2014
DOI: 10.1002/adem.201400104
|View full text |Cite
|
Sign up to set email alerts
|

Wetting and Mechanical Performance of Zirconia Brazed with Silver/Copper Oxide and Silver/Vanadium Oxide Alloys

Abstract: The wetting behavior and mechanical strength of silver/copper oxide and silver/vanadium oxide braze alloys were investigated for both magnesia‐stabilized and yttria‐stabilized (Mg‐PSZ and Y‐TZP) transformation toughened zirconia substrates. The temperatures investigated were 1000–1100 °C, with oxide additions of 1–10 wt% V2O5 or CuO, and hold times of 0.9–3.6 ks. Increasing either the isothermal hold temperature or time had a distinctly negative effect on the joint strength. The maximum strengths for both braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…This revealed that the addition of 5 wt.% CuO into pure Ag can significantly promote the wettability of pure Ag on ZTA ceramic in air. Similar effects of CuO on the wettability of Ag on Al2O3 and YSZ have been reported in previous studies [23,24]. Secondly, the contact angle in the pure Ag/ZTA/N2 wetting system was about 60° higher than that in the pure Ag/ZTA/air wetting system, confirming that oxygen played an important role in reducing the contact angle of pure Ag on ZTA ceramic.…”
Section: Wettability Of Ag-5cuo Alloy On Zta Ceramicsupporting
confidence: 88%
“…This revealed that the addition of 5 wt.% CuO into pure Ag can significantly promote the wettability of pure Ag on ZTA ceramic in air. Similar effects of CuO on the wettability of Ag on Al2O3 and YSZ have been reported in previous studies [23,24]. Secondly, the contact angle in the pure Ag/ZTA/N2 wetting system was about 60° higher than that in the pure Ag/ZTA/air wetting system, confirming that oxygen played an important role in reducing the contact angle of pure Ag on ZTA ceramic.…”
Section: Wettability Of Ag-5cuo Alloy On Zta Ceramicsupporting
confidence: 88%
“…Glass was one of the main filler metals used in RAB, but due to its poor fluidity and high brittleness, pores and cracks easily formed in the joint. Another filler metal was composed of noble metals (Ag, Au, Ag-Pt [20]) and metal oxides (Al 2 O 3 , CuO [21], V 2 O 5 [22]). Compared to the above filler metal systems, Ag-CuO was less expensive and could provide better wettability and toughness.…”
Section: Introductionmentioning
confidence: 99%